Avaliação do potencial do extrato da macroalga marinha kappaphycus alvarezii como fertilizante orgânico, para uso via tratamento de semente e pulverização foliar na cultura de soja - Costa, Matheus Antonio da (2015)
Among the macroalgae grown on a commercial scale today, the red alga Kappaphychus alvarezii noteworthy due to its ease of cultivation and importance as a source of carrageenan extraction, one ficocolóide used in various industrial sectors because of its emulsifying and stabilizing properties. In the process of obtaining this compound, obtained as a byproduct a liquid extract, which has been employed in agriculture. However considering the potential biological activity of oligosaccharides and derivatives, which can be obtained from the solid fraction of seaweed source of carrageenan, the use together of these biomasses, solid and liquid extract biomass, can maximize the efficiency benefits associated with the use of the extract this alga in agriculture. In addition, the high total organic carbon content of that biomass mixture can collaborate in the legal recognition of this potential product as liquid organic fertilizer. The process for obtaining the oligassacarídeos from solid biomass and seaweed, then diluting the liquid extract was acidic hydrolysis. The hydrolytic arranged 2³ factorial arrangement of treatments ranged sulfuric acid solution in 0.2 and 0.4 molar, the temperature at 100 to 127 ° C and reaction time 15 and 30 minutes. The two samples of biomass hydrolyzate that had the highest percentage of organic carbon, and 11.6% and 12.6%, were selected for field trials in soybean, where each sample was diluted in liquid extract at 25% concentrations and 75%. Different doses of these two sample bases and pure liquid extract were tested in seed treatment and foliar spray in soybean. For this first application technology the lowest dose evaluated (2.5 ml kg-1 seed) presented with greater efficiency to increase of growth parameters. And for foliar technology the highest dose evaluated (500 mL ha-1) showed up, apparently more interesting for grain yield increase.